Microbial Applications of Leaves and Stems of Matricaria chamomila Plant Growing at Al–Gabal Al–Khder region - Asma Altarkawi,; Shanzaq Mohammed,; Hamad Hasan, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was carried out on leaves and stems of the Matricaria chamomila plant, which growing at Al –gabal Al –Akhder region, Libya. Two different solvents were used in this study (Aqueous and Methanol). This study was carried out on leaves and stems of Matricaria chamomila. a plant that grows at Al-Gabal Althe Akhder region, Libya. Two different solvents were used in this study (Aqueous and Methanol), where both extracts were used for phytochemical screening and microbial investigation. The photochemical screening and paper chromatograph investigations were applied to the extracts of the studied plants. Also, the anti-microbial activity was carried out on the plant extracts against six types of different species of bacteria, including: (Bacillus cereus, Streptococcus pneumonia, E. coli, Shigella vulgaris, and Pseudomonas aeruginosa), besides two types of Fungi, including (Alternaria alternate and Penicillium). The photochemical screening for the leaf and stem extracts showed the presence of many natural organic compounds as Carbohydrates and/or glycosides, tannins, flavonoids, sterols and/or triterpenes, and saponins. The results also showed variations of the detected compounds in leaves and stems of the studied plant. The paper chromatography analysis showed the presence of flavonoids/phenols and tannins in most of the leaves and stems of the studied plant. Also, the extracts were used for antibacterial and antifungal applications studies, showing different effects on the selected microbial and fungal species in this study, where some of the extracts gave inhibition zones compared with those that did not give any effect on the studied bacteria and fungi.